Skip to content
Related Articles

Related Articles

Improve Article
Save Article
Like Article

ISRO | ISRO CS 2008 | Question 24

  • Last Updated : 20 Nov, 2018

In the expression A'(A’ + B’) by writing the first term A as A + 0, the expression is best simplified as
(A) A + AB
(B) AB
(C) A’
(D) A + B


Answer: (C)

Explanation: A'(A’ + B’)

This expression can be simplified as:
= A'A' + A'B'
= A' + A'B'
= A'(1 + B') // 1 + B' = 1
= A'


Quiz of this Question

My Personal Notes arrow_drop_up
Recommended Articles
Page :